(untitled) (IIUC Business Review, 2026)
Artificial intelligence has become very helpful in an organization’s daily decision-making process. A study is conducted to determine the mediating role of artificial intelligence in the quality of accounting information systems and their perceived organizational performance. The study used an exploratory method to measure the mediating effect where primary data were collected and analyzed. Then, the structural equation model is developed and validated with convergent validity, discriminant validity and model index values in IBM SPSS AMOS 22 software to test the hypotheses. The study results show that the quality of the accounting information system has a significant contribution to the perceived organizational performance without any mediation. Artificial intelligence works as a mediating factor between Accounting Information System (AIS) quality and perceived organizational performance. So, artificial intelligence has a full mediating effect on information system quality and perceived organizational performance. As a result, artificial intelligence has become very important in an organization’s daily decision-making process. The results of this study support the use of artificial intelligence in policy-making and strategy in the daily decision-making process. IIUC Business Review, Vol.-13, Issue-1, December 2024, pp. 59-78